Isolation, pharmacological evaluation and molecular docking studies of bioactive compounds from Grewia optiva - Ul Bari W; Zahoor M; Zeb A; Sahibzada MUK; Ullah R; Shahat AA; Mahmood HM; Khan I (Dove Medical Press, 2019)
Wasim Ul Bari,1 Mohammad Zahoor,1 Alam Zeb,2 Muhammad Umar Khayam Sahibzada,3 Riaz Ullah,4 Abdelaat A Shahat,4,5 Hafiz Majid Mahmood,6 Irfan Khan11Department of Chemistry, University of Malakand, Dir Lower, Chakdara, KPK 18800, Pakistan; 2Department of Biotechnology, University of Malakand, Dir Lower, Chakdara, KPK 18800, Pakistan; 3Department of Pharmacy, Sarhad University of Science and Information Technology, Peshawar, KPK 25000, Pakistan; 4Medicinal, Aromatic and Poisonous Plants Research Center (MAPRC), College of Pharmacy, King Saud University, Riyadh 11451, Saudi Arabia; 5Phytochemistry Department, National Research Centre, Giza, Egypt; 6Department of Pharmacology, College of Pharmacy, King Saud University, Riyadh 11451, Saudi ArabiaCorrespondence: Mohammad ZahoorDepartment of Chemistry, University of Malakand Chakdara, Dir Lower, KPK 18800, PakistanEmail mohammadzahoorus@yahoo.comMuhammad Umar Khayam SahibzadaDepartment of Pharmacy, Sarhad University of Science and Information Technology, Peshawar, KPK 25000, PakistanEmail umar.sahibzada@gmail.comBackground: Traditionally, Grewia optiva is widely used for the treatment of many diseases like dysentery, fever, typhoid, diarrhea, eczema, smallpox, malaria and cough.Methods: Shade-dried roots of G. optiva were extracted with methanol. Based on HPLC results, chloroform and ethyl acetate fractions were subjected to silica column isolation and four compounds: glutaric acid (V), 3,5 dihydroxy phenyl acrylic acid (VI), (2,5 dihydroxy phenyl) 3’,6’,8’-trihydroxyl-4H chromen-4’-one (VII) and hexanedioic acid (VIII) were isolated in pure form. Ellman’s assay was used to determine the anticholinesterase potential of isolated compounds while their antioxidant potential was estimated by DPPH and ABTS scavenging assays.Results: Amongst the isolated compounds, VI and VII exhibited excellent percent inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) (83.23±1.11, 82.72±2.20 and 82.11±2.11, 82.23±1.21, respectively, at 1000 μg/mL) with IC50 of 76, 90, 78 and 92 μg/mL, respectively. Highest percent radicals scavenging against DPPH and ABTS (87.41±1.20 and 86.13±2.31) with IC50 of 64 and 65 μg/mL, respectively, were observed for compound VII. Molecular docking studies also supported the binding of compound VI and VII with the target enzyme. The para-hydroxyl group of the phenolic moiety is formed hydrogen bonds with the active site water molecule and the side chain carbonyl and hydroxyl residues of enzyme.Conclusion: The isolated compounds inhibited the DPPH and ABTS-free radicals, and AChE and BChE enzymes. It was concluded that these compounds could be used in relieving the oxidative stress and pathological symptoms associated with excessive hydrolysis of acetyl and butyryl choline. The results of the study were supported by docking studies for compounds VI and VII.Keywords: G. optiva, antioxidant, acetylcholinesterase, butyrylcholinesterase, molecular docking